Covalent bonding of heme to protein prevents heme capture by nontypeable Haemophilus influenzae. Issue 11 (12th October 2017) - Sgheiza, Valerie; Novick, Bethany; Stanton, Sarah; Pierce, Jeanetta; Kalmeta, Breanne; Holmquist, Melody Frink; Grimaldi, Kyle; Bren, Kara L.; Michel, Lea Vacca
Abstract : Nontypeable Haemophilus influenzae (NTHi) are Gram‐negative pathogens that contribute to a variety of diseases, including acute otitis media and chronic obstructive pulmonary disease. As NTHi have an absolute requirement for heme during aerobic growth, these bacteria have to scavenge heme from their human hosts. These heme sources can range from free heme to heme bound to proteins, such as hemoglobin. To test the impact of heme structural factors on heme acquisition by NTHi, we prepared a series of heme sources that systematically vary in heme exposure and covalent binding of heme to peptide/protein and tested the ability of NTHi to use these sources to support growth. Results from this study suggest that NTHi can utilize protein‐associated heme only if it is noncovalently attached to the protein. Abstract : Nontypeable Haemophilus influenzae (NTHi) are Gram‐negative bacteria that can cause ear infections and chronic obstructive pulmonary disease (COPD). For bacteria such as NTHi, living in human tissues, iron is often a limiting nutrient. One iron source for these bacteria is heme. This study showed that a single covalent bond between heme and a polypeptide is sufficient to prevent heme scavenging by NTHi.